Effects of different preparation protocols of blood serum eyedrops on corneal healing after alkali burn: Clinical evaluation and α-SMA expression - Susiyanti, Made; Widyawati, Syska; Susanto, Eka; Louisa, Melva; Kania, Theresia (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: In cases of alkali burn, blood serum eyedrops may supply protein and growth factors. A standard preparation protocol is necessary for consistency in epitheliotropic capacity. Objective: We aim to evaluate how post-alkali-burn administration of blood serum eyedrops from different preparation protocols results in different outcomes on rabbits. Methods: This randomized experimental study used three treatments: placebo, non-diluted serum, and 25% concentration serum. We analyzed the corneal haziness, neovascularization degree, histopathological examination of neovascularization scores, and alpha-smooth muscle actin (α-SMA) expression. Results: Twelve rabbits (24 eyes) were split evenly into three treatment groups. On day 14, the group receiving the 25% concentration serum had the least corneal haziness (p = 0.005). No adverse effect was observed on the treated eyes. Histopathologically, no significant difference in neovascularization scores and α-SMA expression was observed. Conclusions: Treatment using the 25% concentration serum resulted in less corneal haziness, smaller defect size, and greater healing rate. There was also no significant difference in histopathological outcomes among the three treatment groups.